Service usage of a cohort of formerly homeless women in Aotearoa New Zealand - Brodie Fraser; Maddie White; Hera Cook; Elinor Chisholm; Jenny Ombler; Saera Chun; Hiria Tareha; Nevil Pierse (Elsevier, 2021)
Purpose: The aim of this paper is to explore government service usage across the domains of health, justice, and social development and tax for a cohort of formerly homeless people in Aotearoa New Zealand, focusing specifically on the experiences of women. The Integrated Data Infrastructure is used, which links our de-identified cohort data with administrative data from various Aotearoa New Zealand Government departments. Results: Of the cohort of 390, the majority (53.8%) were women. These women were more likely to be younger (57.1% were aged 25-44), indigenous Māori (78.6%), and have children (81.4%). These women had lower incomes, and higher rates of welfare benefit receipt, when compared to men in the cohort and a control group of women from the wider population. Conclusions: The cohort were primarily female, younger, Māori, and parents. They earned much less than their non-homeless counterparts, and relied heavily on government support. The neoliberalisation of the welfare state, high rates of women's poverty, and the gendered nature of parenthood means that women's homelessness is distinct from men's homelessness.